2021
DOI: 10.1111/bph.15583
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase promotes neointimal hyperplasia by targeting toll‐like receptor 4 (TLR4)–NF‐κB signalling

Abstract: Background and Purpose Neointimal hyperplasia (NIH) is the fundamental cause for vascular diseases and vascular smooth muscle cell (VSMC) dysregulation has been widely implicated in NIH. Neutrophil elastase is a potential therapeutic target for multiple diseases. We investigated the role of neutrophil elastase in VSMC functions and injury‐induced NIH and explored the therapeutic potential of targeting neutrophil elastase in NIH. Experimental Approach VSMCs were used to analyse the effects of neutrophil elastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 77 publications
(139 reference statements)
2
21
0
Order By: Relevance
“…According to our available results, endothelial cells express IMP3 at a relatively low level in the uninjured condition; upon receiving wire‐injured surgery, expression level of IMP3 in endothelial cells followed a trend of early elevation and late decrease. This is highly consistent with the pathological changes of the disease 37,47 . During the early stage of injury, in response to the loss of large number of endothelial cells, the remaining endothelial cells begin to enter a state of proliferation, by up‐regulating the expression of IMP3.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…According to our available results, endothelial cells express IMP3 at a relatively low level in the uninjured condition; upon receiving wire‐injured surgery, expression level of IMP3 in endothelial cells followed a trend of early elevation and late decrease. This is highly consistent with the pathological changes of the disease 37,47 . During the early stage of injury, in response to the loss of large number of endothelial cells, the remaining endothelial cells begin to enter a state of proliferation, by up‐regulating the expression of IMP3.…”
Section: Discussionsupporting
confidence: 81%
“…This is highly consistent with the pathological changes of the disease. 37 , 47 During the early stage of injury, in response to the loss of large number of endothelial cells, the remaining endothelial cells begin to enter a state of proliferation, by up‐regulating the expression of IMP3. Such effect reaches its peak at Day 14; when the endothelial repair process has been largely completed, the demand for cell proliferation is also reduced progressively.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel has been shown to dysregulate the toll-like receptor 4 (TLR4) and the NOD-, LRR-, and pyrin domaincontaining protein 3 (NLRP3) inflammasome [118]. In a noteworthy study, TLR4 was shown to be a target for neutrophil elastase by which this enzyme takes a part in neointimal formation [119].…”
Section: Paclitaxelmentioning
confidence: 99%
“…On another note, Yang et al [ 91 ] performed a study with murine and human aortic tissues. They evidenced a novel mechanism in promoting VSMC migration, proliferation, and inflammation in the setting of intimal hyperplasia, via neutrophil elastase (NE).…”
Section: Spms and The Physiopathology Of Intimal Hyperplasiamentioning
confidence: 99%